Live table fish transportation - a means of innovative value addition in the fish retail markets of Ludhiana, Punjab - Muzaddadi, A. U.; Ahmad, T.; Monika, Monika; Nanda, S. K. (Indian Journal of Fisheries, 2018)
In the present study, different means of transportation of live table fish in Sherpur Fish Market, Ludhiana District in Punjab were investigated. Two methods, one for short distance (travel time